Thematic aid allocation: what are the benefits and risks? - Sebastian Paulo; Heiner Janus; Sarah Holzapfel (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Aid allocation is typically country-based, i.e. focusing first on how to distribute Official Development Assistance (ODA) across countries. Donors consider the needs of developing countries as well as their own interests before deciding which country should receive how much assistance. Subsequently, donor and partner governments choose the thematic areas or sectors of cooperation, such as health, education, the environment, or food security. As an alternative approach, thematic allocation has gained increasing relevance. This form of allocation earmarks funds for specific issues prior to the selection of partner countries. The special initiatives of Germany's Federal Ministry of Economic Cooperation and Development (BMZ) and the United States (US) presidential initiatives for health and food security are prominent examples. The process of aid allocation is crucial for the effective use of scarce public funds. Global changes raise the question to what extent funds should continue to be allocated in a primarily country-based manner or whether a thematic approach is more useful. Historically, development cooperation has evolved as a policy to support poor countries. However, these countries now vary greatly in their development (fragile states, graduated countries, etc.). The North-South logic underlying the term “develop¬ing country” is inconsistent with the universal 2030 Agenda. The Sustainable Development Goals (SDGs) are organised thematically. Many challenges require cross-border solutions (e.g. climate, health, migration). Thematic allocation aligns development cooperation with international challenges. Experience thus far shows both benefits and risks. Thematic allocation can mobilise funding for key issues, bundle resources and raise the visibility of aid. It enables cross-border cooperation, offers room for innovations and is more flexible. Yet, a number of initiatives bypass local capacities and the institutions of partner countries more frequently than country-based allocation does. In other cases, uncoordinated parallel structures arise, which do not take sufficient account of ongoing activities. Thematic allocation is likely to become more important as part of the global effort to achieve the 2030 Agenda. Donors should therefore systematically examine to what extent they want to use thematic allocation in the future. A rigorous assessment can help to better utilise benefits and minimise risks. The key challenge is to make effective use of the more flexible cooperation framework offered by thematic allo¬cation. To this end, donors should sharpen their thematic profiles and select issues according to their comparative advantages. Donors also require adequate organisational structures to be able to coordinate all relevant actors in a given issue area, both internally (e.g. through whole-of-government approaches) and externally working together with a broad range of partners. Ultimately, donors should further strengthen the role of partner countries in thematic programmes and initiatives to ensure that a shift of perspective from countries to themes does not come at the expense of country ownership.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Agenda 2030